Introducing Malaguzzi exploring the life and work of Reggio Emilia's founding father - Smidt, Sandra, 1943- (Routledge, 2013)
"Loris Malaguzzi (1920 - 1994) was the pioneer of the Reggio Emilia approach to teaching young children. An ever-increasing number of teachers and educationalists from all over the world now come to study the Reggio pre-school's unique methods, and this is largely due to Malaguzzi's devotion, work and commitment over 45 years, and the small group of teachers and educators he trained and with whom he developed his methods. The principles that underpin the Reggio Emilia approach are fundamental to the way in which Early Childhood Education is being shaped around the world today. The work of Loris Malaguzzi was rooted in a strong sociocultural framework, meaning it was a considered response to what was needed for particular communities and their needs. Sandra Smidt here considers the life of this remarkable man, and through a pedagogical perspective explores his approach on topics including: - Relationships; - Observation; - Creativity; - Questioning; - Justice; - Equality; - Politics. Accessible and informative, this introductory yet in-depth look at Malaguzzi's life and work will be of huge benefit to anyone working with young children in an educational capacity, including parents, and will be essential reading for students on early childhood education courses"--